(untitled) (Journal of Pathology of Nepal, 2012)
Idiopathic Myelofibrosis is an infrequent chronic myeloproliferative disorder characterized by varying degrees of bone marrow fibrosis and extra medullary hematopoiesis, with the fibrosis being a reactive phenomenon to a neoplastic proliferation of a pluripotent hematopoietic stem cell. Idiopathic Myelofibrosis is heterogeneous in presentation and clinical course, with anemia being one of the most important problems. We present a case of a 59 year old male who presented with severe anemia, the peripheral blood picture mimicking hemolysis with numerous schistocytes and teardrop cells. Journal of Pathology of Nepal (2012) Vol. 2, 323-327 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6888